Advanced Surgical Interventions for Thyroid Diseases from Lobectomy to Total Thyroidectomy - Fazal Rehman, Johar Iqbal, Saeed Khan, Muhammad Arif, Allah Noor, (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To compare the outcomes of lobectomy and total thyroidectomy for thyroid diseases, with a focus on postoperative complications, thyroid hormone levels, and surgical efficacy. Methodology: A retrospective study was conducted between September 2022 and September 2023, involving 370 patients (185 in each surgical group). Data was collected from medical records, including patient demographics, thyroid disease type, surgical technique, postoperative complications, and thyroid hormone levels. Statistical analyses were performed using t-tests and Chi-Square tests to evaluate differences between groups. Results: The study found no significant difference in age, gender, or thyroid hormone levels (T3, T4, TSH) between lobectomy and total thyroidectomy groups. The mean age for lobectomy patients was 45.2 years (SD = 13.1) and for total thyroidectomy patients, it was 47.8 years (SD = 12.6), with no significant difference (p = 0.091). Postoperative complications occurred in 25% (n = 93) of lobectomy patients and 28.6% (n = 106) of total thyroidectomy patients, with no significant difference (p = 0.369). The rates of hypothyroidism, recurrent laryngeal nerve injury, and hypocalcaemia were similar between the two groups. Conclusion: Both lobectomy and total thyroidectomy are effective surgical options for managing thyroid diseases, with similar outcomes in terms of complications and thyroid hormone levels. The choice of procedure should be based on individual patient factors. Further multicenter studies are recommended to validate these findings. Keywords: thyroidectomy, lobectomy, postoperative complications, thyroid hormone levels, papillary thyroid carcinoma.